2019
DOI: 10.1200/jgo.19.00036
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Breast Cancer in Kenya: Presentation, Pathologic Characteristics, and Patterns—Findings From a Tertiary Cancer Center

Abstract: PURPOSE The purpose of this research was to describe the sociodemographic and clinical characteristics of Kenyan women with metastatic breast cancer diagnosed and treated at Aga Khan University Hospital in Nairobi, Kenya from 2012 to 2018. PATIENTS AND METHODS We reviewed charts of Kenyan women with metastatic breast cancer and analyzed sociodemographic data, breast cancer risk factors, and tumor characteristics associated with stage at diagnosis, receptor status (ie, estrogen receptor, progesterone receptor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
(35 reference statements)
4
7
1
3
Order By: Relevance
“…In addition, another study conducted in Kenya showed that 32% of women with breast cancer had metastases at diagnosis studies. 20 In contrast to this study, the major metastasis sites by Ekpe et al 20 were bone (58%), lungs (57%), and liver (50%). In addition, the study in Kenya reported that bone-only metastasis occurred in 39.80% of patients, followed by multiple metastases (33.07%) and lung metastasis (10.94%).…”
Section: Discussioncontrasting
confidence: 76%
“…In addition, another study conducted in Kenya showed that 32% of women with breast cancer had metastases at diagnosis studies. 20 In contrast to this study, the major metastasis sites by Ekpe et al 20 were bone (58%), lungs (57%), and liver (50%). In addition, the study in Kenya reported that bone-only metastasis occurred in 39.80% of patients, followed by multiple metastases (33.07%) and lung metastasis (10.94%).…”
Section: Discussioncontrasting
confidence: 76%
“…To the best of our knowledge, this is the first study to report anastrozole occurrence in Kenyan aquatic ecosystems. The detection of anastrozole could be linked to the rising diagnoses and treatment of breast cancer in the continent and particularly in Kenya [16]. Anastrozole is applied for hormone therapy during breast cancer treatment.…”
Section: Occurrence and Distribution Of Pollutants In Sedimentsmentioning
confidence: 99%
“…3 Even in tertiary facilities, about a third of breast cancer cases are diagnosed in stage four, with metastases to bone, brain, lung or liver. 4 This is associated with high costs of treatment and low overall survival rates. In Kenya, breast cancer occurs earlier in women between ages 35 and 45 years which is 10–15 years earlier than the peak incidence in developed countries.…”
Section: Introductionmentioning
confidence: 99%